Deep phenotyping of unaffected carriers of pathogenic BMPR2 variants screened for pulmonary arterial hypertension - Tóth, Eszter N.; Celant, Lucas R.; Niglas, Marili; Jansen, Samara; Tramper, Jelco; Baxan, Nicoleta; Ashek, Ali; Wessels, Jeroen N.; Marcus, J. Tim; Meijboom, Lilian J.; Houweling, Arjan C.; Nossent, Esther J.; et al. (The European respiratory journal, 2024)
Pathogenic variants in the gene encoding for are a major genetic risk factor for heritable pulmonary arterial hypertension. Owing to incomplete penetrance, deep phenotyping of unaffected carriers of a pathogenic variant through multimodality screening may aid in early diagnosis and identify susceptibility traits for future development of pulmonary arterial hypertension. 28 unaffected carriers (44±16 years, 57% female) and 21 healthy controls (44±18 years, 48% female) underwent annual screening, including cardiac magnetic resonance imaging, transthoracic echocardiography, cardiopulmonary exercise testing and right heart catheterisation. Right ventricular pressure-volume loops were constructed to assess load-independent contractility and compared with a healthy control group. A transgenic rat model was employed to validate findings from humans. Unaffected carriers had lower indexed right ventricular end-diastolic (79.5±17.6 mL·m 62.7±15.3 mL·m ; p=0.001), end-systolic (34.2±10.5 mL·m 27.1±8.3 mL·m ; p=0.014) and left ventricular end-diastolic (68.9±14.1 mL·m 58.5±10.7 mL·m ; p=0.007) volumes than control subjects. rats were also observed to have smaller cardiac volumes than wild-type rats. Pressure-volume loop analysis showed that unaffected carriers had significantly higher afterload (arterial elastance 0.15±0.06 0.27±0.08 mmHg·mL ; p<0.001) and end-systolic elastance (0.28±0.07 0.35±0.10 mmHg·mL ; p=0.047) in addition to lower right ventricular pulmonary artery coupling (end-systolic elastance/arterial elastance 2.24±1.03 1.36±0.37; p=0.006). During the 4-year follow-up period, two unaffected carriers developed pulmonary arterial hypertension, with normal N-terminal pro-brain natriuretic peptide and transthoracic echocardiography indices at diagnosis. Unaffected mutation carriers have an altered cardiac phenotype mimicked in transgenic rats. Future efforts to establish an effective screening protocol for individuals at risk for developing pulmonary arterial hypertension warrant longer follow-up periods.